2007
DOI: 10.1183/09031936.00056507
|View full text |Cite
|
Sign up to set email alerts
|

From registry to quality management: the German Cystic Fibrosis Quality Assessment project 1995–2006

Abstract: Since 1995, the German Cystic Fibrosis Quality Assessment project has collected demographic data and outcome parameters. It aims to develop tools for quality management.The basic data of 6,835 patients has been collected annually by 93 centres. Weight for height and body mass index (BMI) indicated nutritional status, and forced expiratory volume in one second (FEV1) served as the central respiratory parameter. Data on mortality and survival were calculated.The mean age of all patients has increased from 13.9 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
1
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 27 publications
4
69
1
5
Order By: Relevance
“…Therefore, it is considerably difficult to predict the prognosis. In a retrospective study performed by Kerem et al (13) in 1992, it was reported that the two-year mortality was above 50%, if FEV1-expected was ≤30%, PaO 2 was <55 n (%) Chronic (14,15,16,17,18,19,20,21,22). In our study, a FEV1-expected % value of ≤30 was related with increased mortality risk and 75% of these patients were lost in an average period of 2.5 years.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Therefore, it is considerably difficult to predict the prognosis. In a retrospective study performed by Kerem et al (13) in 1992, it was reported that the two-year mortality was above 50%, if FEV1-expected was ≤30%, PaO 2 was <55 n (%) Chronic (14,15,16,17,18,19,20,21,22). In our study, a FEV1-expected % value of ≤30 was related with increased mortality risk and 75% of these patients were lost in an average period of 2.5 years.…”
Section: Discussionmentioning
confidence: 50%
“…In this study, the most valuable variable in determining the prognosis was found to be FEV1 percent. Following this study many studies have been performed to determine the mortality risk in patients with cystic fibrosis (14,15,16,17,18,19,20,21,22). The aim of these studies was to make a right selection for the patients who needed lung transplantation, because even if transplantation is performed, there is a morbidity and mortality risk related to early and late complications (22).…”
Section: Introductionmentioning
confidence: 99%
“…These differences persisted after taking into account socio-economic factors. Similar features can be derived from the CF German Registry where a quality management program with an overall coverage of 82% for the year of 2005 confirmed considerable differences between centres in terms of key parameters (Stern et al, 2008). For instance, the percentage of children (6-18 years) with an FEV 1 above 80% of the predicted value ranged from 20 to 100% in centres treating less than 50 patients and from 35% to 100% in larger centres.…”
Section: Cf Centres Might Not Be Sufficientmentioning
confidence: 55%
“…[2][3][4] Owing to advances in management and treatment of these pulmonary manifestations, the life expectancy of patients is continuously increasing, with a current median survival of approximately 40 years. [3][4][5] Accurate diagnosis and monitoring of CF-related lung disease is crucial in providing early and effective treatment and also in improving the overall prognosis. Thin-sliced chest computed tomography (CT) is the current criterion standard to visualize best the characteristic morphologic pulmonary changes due to its high spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Results: The overall modified Helbich CT score had a mean (SD) of 15. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and median of 15.0 (IQR, 7.3). Without assessment of perfusion, the overall Eichinger score resulted in the following values for CT vs MR examinations: mean (SD), 20.3 (7.2) (range, 4-31); and median, 21.0 (IQR, 9.5) vs mean (SD), 19.5 (7.1) (range, ; and median, 20.0 (IQR, 9.0).…”
mentioning
confidence: 99%